Analysis of methods of regulation of silicon dioxide particles size obtained by the Stober method - Kharchenko, Anastasiia; Myronyuk, Oleksiy; Melnyk, Liubov; Sivolapov, Pavlo (Technology audit and production reserves, 2017)
The object of research is the method of synthesis of silicon dioxide nanoparticles, namely the Stober method. Synthesis of particles with the help of the Stober process is an example of a sol-gel method, one of the most practical and controlled methods for obtaining controlled size nanoparticles, shapes and morphologies. The Stober method is a classical approach to the synthesis of silica nanoparticles, but in existing works there is no systematic approach to establishing a connection between such reaction parameters as the concentration of components, temperature and time of the process. During the research, various types of information retrieval and information research were used. As a result of this work, a survey is obtained that is able to solve the problem of systematizing the influence of these parameters under the conditions of the Stober process. Methods for regulating the size of silica particles are considered, namely, a change in: a temperature in a sufficiently wide range from 5 ºC to 65 ºC; TEOS/H2O/NH3 concentration; quantity and thermodynamic quality of the solvent, as well as the effect of the reaction time. The influence of these parameters is considered not only from the point of view of changing the unit parameter, but also in combination with the others. The regularities of the particle diameter variation for the main synthesis conditions are established. The ways of particle synthesis by the Stober method from hundreds of nanometers to micrometers are shown. It is shown that for the synthesis of particles with minimal dimensions, a decrease in the concentration of the reacting components will be necessary: TEOS, H2O and NH3. This makes it possible to reduce the rate of hydrolysis and condensation processes, as well as the solubility of the intermediate Si(OC2H5)4-X(OH)X], which determines the absence of supersaturation during nucleation. The determining factors for this decrease are the increased synthesis temperature and the use of more polar solvents. The results of the work can be used to control the synthesis of silicon dioxide nanoparticles for various applications, from catalytic systems to functional fillers of materials and in particular to the creation of superhydrophobic structures.